Розрахункове дослідження лопатевих систем робочих коліс здвоєного капсульного прямоточного гідроагрегату - Потетенко, Олег Васильович; Крупа, Євгеній Сергійович; Дранковський, Віктор Едуардович (НТУ "ХПІ", 2009)
In this work the results of numeral research of flow of liquid are presented in running part of the dual hydrounit of capsule type. With the use of the program for the calculation of a bidimentional flows kinematics descriptions of drivings wheels are expected and balances of losses of energy are built in their blade systems.
Keywords: гідротурбіни; відсмоктувальна труба; коефіцієнт швидкохідності